The Adenosine A2A-Receptor Antagonist Istradefylline Enhances the Motor Response of l-DOPA Without Worsening Dyskinesia in MPTP-Treated Common Marmosets - Shin-ichi Uchida; Tomomi Tashiro; Mika Kawai-Uchida; Akihisa Mori; Peter Jenner; Tomoyuki Kanda (Elsevier, 2014)
The adenosine A2A-receptor antagonist istradefylline decreases OFF time in patients with Parkinson's disease who are already treated with optimal doses of dopaminergic medication but can cause an increase in non-troublesome dyskinesia. Preclinical experiments have shown that A2A antagonists are most effective in potentiating motor function when combined with submaximal doses of l-DOPA. However, the effects of combining istradefylline with sub-optimal l-DOPA treatment on established dyskinesia have not been studied. We now examine the effects of acute and repeated administration of istradefylline on dyskinesia in MPTP-treated common marmosets previously primed to exhibit involuntary movements by prior exposure to l-DOPA. In these animals, single dose acute oral administration of istradefylline (10 mg/kg) enhanced and prolonged the anti-parkinsonian effects of a sub-optimal dose of l-DOPA (2.5 mg/kg). The chronic co-administration of istradefylline (10 mg/kg) with l-DOPA (2.5 mg/kg) for 21 days did not worsen the severity of existing dyskinesia. Rather, the severity of dyskinesia tended to be reduced over the 21-day treatment period. These results suggest that istradefylline can be used to potentiate the effects of sub-optimal doses of l-DOPA in the treatment of Parkinson's disease without causing or worsening dyskinesia. Keywords:: anti-parkinsonian, adenosine A2A-receptor antagonist, l-DOPA, dyskinesia, MPTP